A plant factory for moth pheromone production - Ding, Bao-Jian; Hofvander, Per; Wang, Hong-Lei; Durrett, Timothy P.; Stymne, Sten; Löfstedt, Christer (My University, 2014)
Moths depend on pheromone communication for mate finding and synthetic pheromones are used for monitoring or disruption of pheromone communication in pest insects. Here we produce moth sex pheromone, using Nicotiana benthamiana as a plant factory, by transient expression of up to four genes coding for consecutive biosynthetic steps. We specifically produce multicomponent sex pheromones for two species. The fatty alcohol fractions from the genetically modified plants are acetylated to mimic the respective sex pheromones of the small ermine moths Yponomeuta evonymella and Y. padella. These mixtures are very efficient and specific for trapping of male moths, matching the activity of conventionally produced pheromones. Our long-term vision is to design tailor-made production of any moth pheromone component in genetically modified plants. Such semisynthetic preparation of sex pheromones is a novel and cost-effective way of producing moderate to large quantities of pheromones with high purity and a minimum of hazardous waste.
Keywords: Moths; Pheremones; Moth sex pheromone; Nicotiana benthamiana